2015
DOI: 10.1016/j.amepre.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

The Whole-of-School Approach to Physical Activity

Abstract: Introduction The IOM recommends schools adopt a Whole-of-School (WOS) approach—one that is comprehensive, coordinated, and provides opportunities for students to be active before, during, and after school. This study examined, in a nationally representative sample of secondary students in the conterminous U.S.: (1) the degree of implementation of a WOS approach; and (2) the association between WOS implementation and student physical activity. Methods A WOS index—based on six school practices—was calculated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…For example, a national study found that, on average, middle school students attend schools that implemented only 4 out of the 6 physical activity policies and practices that were examined (i.e., shared use, intramural sports, interscholastic sports, active transport, activity breaks, recommended amounts of PE). 27 Importantly, middle school students who attended schools that implemented more physical activity practices and policies were physically active for at least 60 minutes on more days compared to students who attended schools with fewer physical activity practices and policies in place . 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a national study found that, on average, middle school students attend schools that implemented only 4 out of the 6 physical activity policies and practices that were examined (i.e., shared use, intramural sports, interscholastic sports, active transport, activity breaks, recommended amounts of PE). 27 Importantly, middle school students who attended schools that implemented more physical activity practices and policies were physically active for at least 60 minutes on more days compared to students who attended schools with fewer physical activity practices and policies in place . 27 …”
Section: Discussionmentioning
confidence: 99%
“…27 Importantly, middle school students who attended schools that implemented more physical activity practices and policies were physically active for at least 60 minutes on more days compared to students who attended schools with fewer physical activity practices and policies in place . 27 …”
Section: Discussionmentioning
confidence: 99%
“…The results support school programs designed to maintain or improve CRF among students and suggest that such programs should be continued throughout the duration of middle school. The Institute of Medicine promotes a whole‐of‐school approach to increasing opportunities for physical activity . Research has shown that middle school students attending schools with greater implementation of the whole‐of‐school approach had higher rates of physical activity than students attending schools where the approach was implemented to a lesser extent .…”
Section: Implications For School Healthmentioning
confidence: 99%
“…The Institute of Medicine promotes a whole‐of‐school approach to increasing opportunities for physical activity . Research has shown that middle school students attending schools with greater implementation of the whole‐of‐school approach had higher rates of physical activity than students attending schools where the approach was implemented to a lesser extent . However, where a whole‐of school approach is not feasible, studies have shown that effective physical activity interventions can occur during: Recess Classroom‐based physical activity breaks PE classes After‐school programs …”
Section: Implications For School Healthmentioning
confidence: 99%
“…Thus, for students to achieve recommended levels of PA at school, a whole-of-school (WOS) approach to PA curriculum was developed, which promotes PA opportunities outside PE class—including recess, classroom PA time, active transport, before- and after-school programming, and intramural and extramural sports [3]. Researchers using a WOS index (scored 0–6), comprised of six school practices for promoting/providing PA, found that 66% of middle schools in a national sample scored ≤4 [8]. Thus, such schools have room for improvement and should identify missing practices to increase students’ PA level.…”
Section: Introductionmentioning
confidence: 99%